1998
DOI: 10.2136/sssaj1998.03615995006200010006x
|View full text |Cite
|
Sign up to set email alerts
|

Flow Velocity Effects on the Retardation of FD&C Blue no. 1 Food Dye in Soil

Abstract: Dyes are often used as tracers of water and solute flow in soil. However, there has been little published research on the effects of flow velocity on the relative movement of dye and wetting fronts. Recently, the FD&C Blue no. 1 dye has been used as a tracer of preferential water flow paths in soils, and has attractive properties suggesting it will be used increasingly in the future. The objective of this study was to characterize the effects of flow velocity on the adsorption characteristics of the FD&… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 0 publications
0
24
0
Order By: Relevance
“…At this concentration, it should remain visible after considerable dilution and adsorption (German-Heins and Flury, 2000). The non-linearity of the sorption isotherm measured for Brilliant Blue (Perillo et al, 1998;Ketelsen and Meyer-Windel, 1999;German-Heins and Flury, 2000;Morris et al, 2008) will result in a self-sharpening front that provides a clear contrast with soil. The pulse application of dye used for this experiment was calculated to achieve an average concentration of approximately 3-6 gL − 1 dye after dilution by the rainfall to ensure good visibility.…”
Section: Methodsmentioning
confidence: 97%
“…At this concentration, it should remain visible after considerable dilution and adsorption (German-Heins and Flury, 2000). The non-linearity of the sorption isotherm measured for Brilliant Blue (Perillo et al, 1998;Ketelsen and Meyer-Windel, 1999;German-Heins and Flury, 2000;Morris et al, 2008) will result in a self-sharpening front that provides a clear contrast with soil. The pulse application of dye used for this experiment was calculated to achieve an average concentration of approximately 3-6 gL − 1 dye after dilution by the rainfall to ensure good visibility.…”
Section: Methodsmentioning
confidence: 97%
“…This dye was chosen because it is a good compromise between visibility, mobility, and toxicity for visualizing flow pathways in the vadose zone (German-Heins and Flury, 2000). The properties of Brilliant Blue FCF have been studied in detail by Flury and Flühler (1995), GermanHeins and Flury (2000), Ketelsen and Meyer-Windel (1999), and Perillo et al (1998). The sorption isotherm of this substance is often highly non-linear (Ketelsen and Meyer-Windel, 1999;Perillo et al, 1998).…”
Section: Study Sitesmentioning
confidence: 99%
“…The properties of Brilliant Blue FCF have been studied in detail by Flury and Flühler (1995), GermanHeins and Flury (2000), Ketelsen and Meyer-Windel (1999), and Perillo et al (1998). The sorption isotherm of this substance is often highly non-linear (Ketelsen and Meyer-Windel, 1999;Perillo et al, 1998). When applied at a concentration of 4 g l À 1 , Brilliant Blue FCF is still visible after considerable dilution and adsorption over flow distances (German-Heins and Flury, 2000).…”
Section: Study Sitesmentioning
confidence: 99%
“…Several studies have reported discrepancies between the K values of organic compounds determined by batch and column techniques. In most cases, the batch-determined values were higher than their column-determined counterparts (Bilkert and Rao 1985;Celorie et al 1989;Gaber et al 1992;Piatt et al 1996;Maraqa et al 1998Maraqa et al , 2011Maraqa 2001a;Thorbjarnarson and Mackay 1994b;MacIntyre et al 1991;Carmichael et al 1999;Bouchard et al 1988;Perillo et al 1998;Thomsen et al 1999;Kazemi et al 2008;Hanna et al 2012). The level of discrepancy between the batch-and column-determined K varies from slight differences (Bouchard et al 1988;Celorie et al 1989;Maraqa et al 1998;Maraqa 2001a) to differences that reached orders of magnitude (Piatt et al 1996).…”
Section: Relevance To Previous Studiesmentioning
confidence: 88%